Access to Cancer Care and General Medical Care Services Among Cancer Survivors in the United States: An Analysis of 2011 Medical Expenditure Panel Survey Data. (November 2016) - de Moor, Janet S.; Virgo, Katherine S.; Li, Chunyu; Chawla, Neetu; Han, Xuesong; Blanch-Hartigan, Danielle; Ekwueme, Donatus U.; McNeel, Timothy S.; Rodriguez, Juan L.; Yabroff, K. Robin
Objectives: Cancer survivors require appropriate health care to manage their unique health needs. This study describes access to cancer care among cancer survivors in the United States and compares access to general medical care between cancer survivors and people who have no history of cancer. Methods: We assessed access to general medical care using the core 2011 Medical Expenditure Panel Survey (MEPS). We assessed access to cancer care using the MEPS Experiences With Cancer Survey. We used multivariable logistic regression to compare access to general medical care among 2 groups of cancer survivors (those who reported having access to all necessary cancer care [n = 1088] and those who did not [n = 70]) with self-reported access to general medical care among people who had no history of cancer (n = 22 434). Results: Of the 1158 cancer survivors, 70 (6.0%) reported that they did not receive all necessary cancer care. Adjusted analyses found that cancer survivors who reported not receiving all necessary cancer care were also less likely to report receiving general medical care (78.0%) than cancer survivors who reported having access to necessary cancer care (87.1%) and people who had no history of cancer (87.8%). Conclusions: This study provides nationally representative data on the proportion of cancer survivors who have access to necessary cancer care and yields insight into factors that impede survivors' access to both cancer care and general medical care. This study is a reference for future work on access to care.